Cytotoxic carbazole alkaloids from Murraya koenigii (Rutaceae) - Md. Sukari, Mohd. Aspollah; Ismail, N.; Abu Bakar, Noor Haslizawati; Ithnin, Nur Liyana (2014)
Crude extracts and isolated compounds from leaves, stem bark and roots of Murraya koenigii including (1) mahanimbine, (2) girinimbine, (3) murrayacine, (4) murrayanine, (5) murrayafoline A. and (6) 3-methylcarbazole were screened for cytotoxic activity against HL-60 cancer cell lines (human T-promyelocytic leukemia), MCF-7 cancer cell lines (human breast cancer), HT-29 cancer cell lines (human colon cancer) and HeLa cancer cell lines (human cervical carcinoma cancer). The cytotoxic potential of the isolated compounds was determined by using MTT (3-[4,5-dimethyl-2-thiazolyl]-2-5-diphenyl-2H-tetrazolium bromide) method. Most of the tested samples showed strong activity against four cancer cell lines with IC50 value less than 30 μg/ml.